Penerapan Arkas Dalam Pemenuhan Standar Mutu Sarana Dan Prasarana Sekolah - Ambrosius Tode Peya Nia Do; Laila Sari Ramadhan; Mentari Putriwulan; Unifah Rosyidi; Muh. Takdir (Departement of Mathematics Education, 2025)
The purpose of this study is to evaluate the implementation of Aplikasi Rencana Kegiatan dan Anggaran Sekolah (ARKAS) in fulfilling the quality standards of school facilities and infrastructure. ARKAS was developed by the Ministry of Education and Culture Republic of Indonesia as a digital system for transparent, accountable and efficient school budget management. This research uses the library research method to collect and analyze data from various relevant sources. The results show that the implementation of ARKAS has a positive impact on school budget management. ARKAS improves transparency, accountability and efficiency in budget planning, reporting and evaluation. In addition, ARKAS assists schools in meeting the quality standards of facilities and infrastructure set by the government, so that they can support an effective and quality learning process. The case study also shows that schools that successfully implement ARKAS can improve the quality of facilities and infrastructure optimally. The conclusion of this study is that ARKAS is an effective tool in managing school budgets and meeting the quality standards of facilities and infrastructure. Strategies are needed to optimize the implementation of ARKAS through collaboration with stakeholders, continuous monitoring and evaluation, and increasing user capacity through regular training.